The Relationship Between Motivation And Family Support And Adherence To Oat Therapy Among Patients With Pulmonary Tuberculosis In The Service Area Of The Batujaya Community Health Center In Karawang - Suryanto, Yanto; Pebriani, Emi; Junika, Adep; Mudrika, Riska; Rohaiti, Eti (Student Scientific Journal, 2026)
Pulmonary tuberculosis (TB) remains a public health problem in Indonesia. The success of TB treatment is greatly influenced by patient compliance in taking Anti-Tuberculosis Drugs (OAT). Low motivation and lack of family support can cause patients to be non-compliant in taking OAT, thereby increasing the risk of treatment failure. This study aims to determine the relationship between motivation and family support with adherence to taking OAT in pulmonary TB patients at Batujaya Community Health Center in 2026. This study used a quantitative method with a cross-sectional approach. The study population was 114 pulmonary TB patients with a sample of 53 respondents selected using proportional purposive sampling technique. Data collection used a questionnaire and analyzed using the chi-square test. The results showed a relationship between motivation and adherence to taking OAT with a p-value = 0.000 (